Effect of mixed meal replacement of soybean meal on growth performance, nutrient apparent digestibility, and gut microbiota of finishing pigs - He, Zhentao; Liu, Shuai; Wen, Xiaolu; Cao, Shuting; Zhan, Xianliang; Hou, Lei; Li, Yaojie; Chen, Shaozhen; Zheng, Huayu; Deng, Dongyan; Gao, Kaiguo; Yang, Xuefen; et al. (Frontiers in Veterinary Science, 2024)
This study was carried out to investigate the effects of mixed meal (rapeseed meal, cotton meal, and sunflower meal) replacement soybean meal on growth performance, nutrient apparent digestibility, serum inflammatory factors and immunoglobulins, serum biochemical parameters, intestinal permeability, short-chain fatty acid content, and gut microbiota of finishing pigs. A total of 54 pigs with an average initial weight of 97.60 ± 0.30 kg were selected and randomly divided into 3 groups according to their initial weight, with 6 replicates in each group and 3 pigs in each replicate. The trial period was 26 days. The groups were as follows: control group(CON), fed corn-soybean meal type basal diet; Corn-soybean-mixed meal group(CSM), fed corn-soybean meal-mixed meal diet with a ratio of rapeseed meal, cotton meal, and sunflower meal of 1:1:1 to replace 9.06% soybean meal in the basal diet; Corn-mixed meal group(CMM), fed a corn-mixed meal diet with a ratio of Rapeseed meal, Cotton meal and Sunflower meal of 1:1:1 to replace soybean meal in the basal diet completely. The crude protein level of the three diets was maintained at 12.5%. Our findings revealed no significant impact of replacing soybean meal with the mixed meal (rapeseed meal, cotton meal, and sunflower meal) on the ADG (Average daily gain), ADFI (Average daily feed intake), and F/G (Feed gain ratio) (P > 0.05), or crude protein, crude fat, and gross energy (P > 0.05) in the diet of finishing pigs. This study demonstrated that the mixed meal (rapeseed meal, cotton meal, and sunflower meal) as a substitute for soybean meal in the diet had no significant negative effects on the growth performance, nutrient apparent digestibility, serum immunoglobulins, serum antioxidant capacity, intestinal permeability, short-chain fatty acid content, and diversity of gut microbiota of finishing pigs. These results can help develop further mixed meals (rapeseed meal, cotton meal, and sunflower meal) as a functional alternative feed ingredient for soybean meals in pig diets.